Split Anterolateral Thigh Flap: A New Classification of Anatomical Variants and a Surgical Planning Algorithm - Shih, Hsiang-Shun; Chiu, Ting-Han; Jeng, Seng-Feng; Chen, Jill (Journal of Reconstructive Microsurgery, 2024)
Background Split anterolateral thigh flap is a versatile reconstruction option, yet long underestimated as no practical perforator classification and no optimal strategy were present. Harvesting “capillary nonsizable perforators” could potentially expand flap splits to those with no existing multiple sizable perforators. Concerns over defect characteristics, recipient vessels, pedicle length, and split timing should all be weighted equally in designing the suitable flap. Refinement is thus required to enable precise reconstructions.Methods All patients undergoing anterolateral thigh flap harvests between 2014 and 2021 performed by a single surgeon were included. The perforator patterns of sizable pedicle, course, origin, and further successful flap-split methods were documented. Surgical outcome of flap survival was analyzed.Results Anatomical variants of 134 (48.4%) dual, 123 (44.4%) single, and 20 (7.2%) no sizable perforators were found in a total of 277 anterolateral thigh flaps. The overall flap survival rate was 97.5%. Flap split was performed in 82 flaps, including 29 single and 5 no sizable perforator cases previously considered “unsplittable,” by utilizing a series of direct skin paddle split, capillary nonsizable perforators harvesting, and flow-through anastomosis technique. Comparable flap survivals were found between split and nonsplit flaps as well as between split segments supplied by sizable and capillary nonsizable perforators. Primary closure was achieved in 98.9% of the thigh donor sites.Conclusion A new classification of the common anterolateral thigh flap anatomical variants was proposed and a comprehensive algorithm of split flap strategy was developed along with the innovative “fabricate” concept.
Keywords: ALT; split; microsurgery